Cut face roughness analysis under waterjet cutting - Alexey V. Verchenko; Mikhail A. Tamarkin; Alexander A. Kishko (Advanced Engineering Research)
Introduction. The feeding effect on the cut face surface under waterjet cutting is considered. Cutting is done by water and abradant mixture emitted from the nozzle at high speed and high pressure. Under the cutting jet action, the erosion damage of the material occurs, the abrasive particles remove the microchipping layer, and water evacuates them from the cutting zone. Waterjet cutting can process almost any material.The cutting process is "cold", there is no thermal effect on the metal. It is possible to cut both 3D and 5D complex geometries, for example, to preprocess bladed integrated disks of the gas-turbine engines. Materials and Methods. The research was carried out on the basis of the JSC "Rostvertol" enterprise on the waterjet cutting plant of the Flow company. The materials most frequently used in the aircraft industry were chosen: steel 30 KhGSA, aluminum alloy D16Т, and composite material (fiberglass-titanium). The recommendations that allow reducing the number of defects under the waterjet cutting are given. Research Results. The effect of the waterjet-cutting nozzle feeding on the cut face roughness is theoretically investigated. The dependences of the surface roughness determination for the distinguished segment of the cut face are obtained. The experimental studies confirming the adequacy of the theoretical models obtained are performed. Discussions and Conclusions. As a result of the studies, it is found that the roughness of the treated surface deteriorates with increase in feeding. Furthermore, the deterioration is nonuniformly distributed along the cross- section of the cut. To reduce the width of the corrugated cut, the feedrate should be reduced.